Data - Chalmandrier, Loïc; Münkemüller, Tamara; Devictor, Vincent; Lavergne, Sébastien; Thuiller, Wilfried (Dryad Digital Repository, 2014)
The datafile contains five files: (1) The site by species matrices of the four studied regions. Row labels indicate the identity of the site and the year of sampling separated by "_". (2) the functional tree of 217 bird species from France in Newick format, see supplementary material for details about its construction.